Efficient Plant regeneration through leaf, In vitro Flowering and Biochemical studies during morphogenesis of Solanum nigrum L. - J. Aslam , Mahmooduzzafar, M.Y. Zargar, M.A. Bhat, P. Ahmad A. Mujib (Journal of Phytology, 2009)
In this investigation, Murashige and Skoog (MS) medium when supplemented with 6-benzylamino purine (BAP) or Kinetin produced high frequency of in vitro shoot directly from in vitro raised Solanum nigrum leaves without any callusing stage. Among the plant growth regulators (PGRs) the best response was noted at 2.0 mgl-1 BAP and 1.5 mgl-1 kinetin. Shoot formation and multiplication were more pronounced on dorsal leaf surface (0.5-1.5 cm2) compared to ventral. Biochemical studies including soluble protein, sugar and amino acid were carried out in order to know the differences in reserves of some biochemical entities. Nearly all parameters were high in samples derived from dorsal leaf, which was grown in MS augmented with 2.0 mgl-1 BAP or 1.5 mgl-1kinetin. The present investigation also describes first successful induction of in vitro flowering in S. nigrum, which can augment selective hybridization. Finally, the in vitro raised shoots were treated with various concentrations of auxins for obtaining roots, the rooted plantlets were transplanted with 100% survival in field conditions.